A systematic review and meta-analysis on serum and salivary levels of total antioxidant capacity and C-reactive protein in oral lichen planus patients. (August 2022) - Hatami, Masoud; Rezaei, Mahya; Sadeghi, Masoud; Tadakamadla, Jyothi; Pekiner, Filiz Namdar; Mozaffari, Hamid Reza
Abstract: Objective: Oral lichen planus (OLP) is an inflammatory disease that total antioxidant capacity (TAC) and C-reactive protein (CRP) play an important role in its pathogenesis. In this meta-analysis, we compared the salivary and serum levels of TAC and CRP between OLP patients and controls. Design: A comprehensive search was performed in four databases (PubMed, Scopus, Web of Science, and Cochrane Library). Standardized mean difference (SMD) and 95% confidence intervals (CI) were computed by the RevMan 5.3. Sensitivity analysis, subgroup analysis, meta-regression, and publication bias were analyzed by the CMA 2.0. Results: Nineteen articles were included in the meta-analysis. The pooled SMDs were -1.80 μmol/L (95%CI: -2.75, -0.85; p = 0.0002) and -2.56 μmol/L (95%CI: -4.40, -0.72; p = 0.006) for the salivary and serum levels of TAC, respectively. The SMDs for salivary and serum levels of CRP were 0.64 μg/L (95%CI: 0.35, 0.94; p < 0.0001) and 0.97 mg/L (95%CI: 0.56, 1.338; p < 0.00001), respectively. Geographical area based on the country was a significant factor in the subgroup analysis for salivary TAC level. There was adequate evidence supporting the occurrence of less salivary and serum TAC levels in OLP patients than controls, but the amount of information was inadequate to make valid conclusions for salivary CRP level. Conclusions: In OLP patients, salivary and serum levels of TAC is significantly lower while the salivary and serum levels of CRP is significantly higher than controls. Highlights: Low salivary level of total antioxidant capacity was observed in oral lichen planus patients than the controls. Low serum level of total antioxidant capacity was observed in oral lichen planus patients than the controls. There was a higher serum level of C-reactive protein in oral lichen planus patients compared to the controls. Salivary level of C-reactive protein was higher in oral lichen planus patients than the controls.